Recent advances and developments in COVID‐19 in the context of allergic diseases. Issue 7 (21st September 2021) - Ding, Mei; Dong, Xiang; Sun, Yuan‐li; Sokolowska, Milena; Akdis, Mübeccel; van de Veen, Willem; Azkur, Ahmet Kursat; Azkur, Dilek; Akdis, Cezmi A.; Gao, Ya‐dong
Abstract: Background: Since the first reports of coronavirus disease 2019 (COVID‐19) in Wuhan, China, in December 2019, there have been 198 million confirmed cases worldwide as of August 2021. The scientific community has joined efforts to gain knowledge of the newly emerged virus named severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), the immunopathological mechanisms leading to COVID‐19, and its significance for patients with allergies and asthma. Methods: Based on the current literature, recent advances and developments in COVID‐19 in the context of allergic diseases were reviewed. Results and Conclusions: In this review, we discuss the prevalence of COVID‐19 in subjects with asthma, attacks of hereditary angioedema, and other allergic diseases during COVID‐19. Underlying mechanisms suggest a protective role of allergy in COVID‐19, involving eosinophilia, SARS‐CoV‐2 receptors expression, interferon responses, and other immunological events, but further studies are needed to fully understand those associations. There has been significant progress in disease evaluation and management of COVID‐19, and allergy care should continue during the COVID‐19 pandemic. The European Academy of Allergy & Clinical Immunology (EAACI) launched a series of statements and position papers providing recommendations on the organization of the allergy clinic, handling of allergen immunotherapy, asthma, drug hypersensitivity, allergic rhinitis, and other allergic diseases. Treatment of allergies using biologics during the COVID‐19 pandemic has also been discussed. Allergic reactions to the COVID‐19 vaccines, including severe anaphylaxis, have been reported. Vaccination is a prophylactic strategy that can lead to a significant reduction in the mortality and morbidity associated with SARS‐CoV‐2 infection, and in this review, we discuss the proposed culprit components causing rare adverse reactions and recommendations to mitigate the risk of anaphylactic events during the administration of the vaccines.